THE ANALYSIS OF INTERLANGUAGE PRODUCED BY 3RD GRADE HIGH SCHOOL STUDENTS IN NARRATIVE WRITING TEXT - Nida Amalia Asikin (University of Kuningan, 2017)
This research is a descriptive case study concerning interlanguage in EFL students’ narrative writing. The study explores the occurrence of interlanguage in students’ writing, and the reason(s) why interlanguage exist in their writing. The data of the study are ten narrative texts produced by nine twelfth-year students of a senior high school in Kuningan. The study used a qualitative research design. There was one data collection procedures applied in this study, namely document analysis. The data from students’ texts were analyzed on the basis of the concept of interlanguage by Selinker (1972). The results of the study revealed that from the ten texts, the interlnguage appear in forming passive sentence, choosing incorrect verb agreement, choosing wrong auxiliary, making the unparalleled sentence, and translating sentence word by word. For that reason, it is concluded that interlanguage exist due to the strong influence of native language. Therefore, it is suggested that students should be exposed to the use of appropriate English grammar in their writing.Keywords: interlanguage, narrative writing, passive sentence